Die US-Inflationsbekämpfung 1966-1970: Einige Konsequenzen für die Bundesrepublik Deutschland - Dieter Cassel; H. Jörg Thieme (Kredit und Kapital, 1971)
Combatting Inflation in the USA, 1966 - 1970: Some Consequences for the Federal Republic of Germany The path of the Federal Republic of Germany from the price level stability of 1967/68 to the current acceleration of inflation has some parallels with developments in the USA. In order to avoıd a repetition in the Federal Republic of Germany of the US economic policy mistakes since 1965, the most important stabilization policy measures are described and their effects interpreted from the monetary standpoint. It becomes evident that not only the inflation itself causes costs to the national economy, but also the combatting of inflation. The further the inflation process has progressed, the higher are those costs. At the present time, however, the theoretical groundwork is lacking for a short-term, optimal-cost and politically practicable stabilization programme. As shown by a critical examination of Friedmann's and Brunner's approaches the monetarist theories also provide no politically exploitable information as yet on the ratio in which the damping effect of monetary restrictions is broken down into price and output effects. As long as this splitting problem is unsolved, the economic costs of stabilization policy cannot be calculated. This makes them a shuttlecock for widely differing interests, whose growing influence prevent a solution of the inflation problem. For the Federal Republic of Germany, the consequences are as follows: The observed shift of responsibility for inflationary processes as a result of the ground gained by non-monetary inflation theories must unequivocally be transfered back to the Government and the Bundesbank. The latter should make the best of the already high costs of combatting inflation before they become completely intolerable politically and inflation becomes a permanent phenomenon sanctioned in the interests of pressure groups. In the long run, the best strategy consists in not allowing inflationary trends even to start. To attain this goal, however, a change in economic policy conceptions would be necessary, the contours of which are outlined
Keywords: 330